Determining Factors of Food Habits of Teenagers in Consuming Modern and Traditional Fast Foods - Derick Thiana; Diah K Pranadji; . Retnaningsih (Media Gizi dan Keluarga, 2000)
The objective of this research was to investigate factors that influenced food habits of teenagers in consuming modern and traditional fast foods. The subjects were 186 high school students in Jakarta. The average of pocket money of the subjects was Rp 2880 – 3870 per day. The knowledge about modern and traditional fast food was moderate and the attitude was neutral. The most frequent of modern fast food to be consumed was fried chicken, whereas traditional fast food was meatballs, with average consumption is 8-12 times per month. Factor that influenced food habits of teenagers in consuming modern and traditional fast food was attitude.